Perceptions of social norms around healthy and environmentally-friendly food choices: Linking the role of referent groups to behavior - Çoker, Elif Naz; Jebb, Susan A.; Stewart, Cristina; Clark, Michael; Pechey, Rachel (Frontiers in Psychology, 2022)
Referent groups can moderate the perception of social norms and individuals’ likelihood to model them norms in food choice contexts, including vegetable intake and reduced meat consumption. The present study investigated whether having a close vs. a distant social group as the referent changed perceptions of social norms around making healthy and eco-friendly food choices. It also assessed whether these changes were associated with a difference in food choice in a virtual grocery shopping task. A nationally representative sample of UK adults (N = 2488) reported their perceptions of making healthy and eco-friendly food choices being the norm among people they share meals with (close referent group) and most people in the UK (distant referent group). The former was more commonly perceived to be making both healthy (Z= -12.0, p <.001) and eco-friendly (Z= -13.27, p < .001) food choices than the latter. Perceptions of norms referring to the close group were significantly associated with the environmental (β = -.90, 95% CIs: -1.49, -.28) and health (β = -.38 p < .05, 95% CIs: -.68, -.08) impacts of participants’ food choices in a virtual shopping task. No such relationship was found for norms referring to the distant group for both environmental (β =.43, 95% CIs: -1.12, .25) and health (β = -.06, p > .05, 95% CIs: -.37, .25) impacts. Framing social norms around making healthy and eco-friendly food choices to refer to a closer referent group may change their perceptions and ability to encourage sustainable and healthy food purchasing.